Dosage design for natural medicinal products - Ahmad, Kausar (2015)
Natural medicinal products (NMPs)based especially on herbs and various plants are enjoying growing popularity. The notion that natural ingredients would have less side effects compared to conventional allopathic medicines appear to be the driving factor for the increasing number of NMPs in the market. However, the quality of active ingredients may sometimes have adverse effects. Reports on the quality of NMPs indicated presence of harmful organisms, heavy metals and adulteration. Further, some therapeutic claims made for the NMPs are not substantiated. This will also hinder marketability of NMPs. The quality of various kinds of excipients can also be a factor in the overall quality of NMPs. Examples of NMPs are given.